A higher baseline plasma uric acid level is an independent predictor of arterial stiffness: A community-based prospective study. Issue 6 (February 2017) - Ding, Xiao-Han; Wang, Xiaona; Cao, Ruihua; Yang, Xu; Xiao, Wenkai; Zhang, Yun; Bai, Yongyi; Wu, Hongmei; Ye, Ping
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: Hyperuricemia has been demonstrated to be a risk factor for cardiovascular diseases. Though the association between uric acid (UA) and arterial stiffness has been investigated previously in patients with basic diseases, the predictive value of baseline UA level for arterial stiffness has not been conducted. We aimed at identifying the predictive role of UA for arterial stiffness prospectively. A longitudinal follow-up study in a routine health check-up population was performed with an average follow-up of 4.8 years. The demographic information, baseline and follow-up anthropometric parameters, arterial stiffness (pulse-wave velocity, PWV), and biomarker variables including UA have been measured and analyzed. A total of 1447 valid follow-ups were available for the final analysis. Both of the baseline and follow-up UA levels were significantly higher in the arterial stiffness groups than that in the nonarterial stiffness groups (all P values <0.001). The follow-up carotid-femoral PWV [(cf-PWV), r  = 0.161, P  < 0.001] was strongly correlated with baseline UA. At the follow-up cross-section, cf-PWV was also closely associated with UA ( r  = 0.101, P  < 0.001). Logistic regressions revealed that a higher baseline UA level was an independent predictor of follow-up arterial stiffness assessed by cf-PWV [odds ratio (OR): 1.824; P  = 0.046]. A higher baseline level of UA is closely related to arterial stiffness and is an independent predictor of arterial stiffening.